Access to electronic and print information resources by people with visual impairments in university libraries: A review of related literature. Issue 6 (13th August 2018) - Majinge, Rebecca Mgunda; Mutula, Stephen Mudogo
Abstract : Purpose: The purpose of this paper is to discuss the implication of copyright on access to electronic and print information resources by people with visual impairments in university libraries. The paper examines the extent to which electronic and print information resources in university libraries are accessible to people with visual impairments; the extent to which existing national/international copyright laws facilitate or hamper access to electronic and print information resources by people with visual impairments; examine challenges facing people with visual impairments in accessing electronic and print information resources; and how these challenges can be ameliorated. Design/methodology/approach: The paper is based on review of empirical and theoretical literature and is underpinned by Oliver's (1990) social model of disability. Findings: The findings reveal that many university libraries the world over lack the capacity to offer an effective information service to people with visual impairments. Furthermore, the stringent copyright laws and licensing regimes for purchasing or transcribing content from one format to another make provision of information services to people with visual impairments difficult. In-university libraries are faced with various challenges in accessing electronic and print information that include among others copyright and licensing restrictions, and system design issues. Assistive technologies (ATs), enabling policies, skilled staff and facilitative copyright regimes can help ameliorate some of these barriers. Practical implications: ATs, enabling policies, skilled staff and facilitative copyright regimes are key to unlocking the barriers that hinder people with visual impairments from effectively accessing print and electronic resources in university libraries. Protection of the basic rights of persons with disabilities including visual impairments, the elimination of social discrimination and bridging the accessibility gap are integral to social inclusion. This paper provides the basic information to university libraries for addressing challenges associated with access to electronic and print resources by people with visual impairments. Social implications: Access to information to all including people with visual impairments in society is a basic human and moral right that every human being must enjoy. The Sustainable Development Goals' 2030 agenda for sustainable development envisages a world of universal respect for human rights and human dignity […] equality and non-discrimination, an equitable, tolerant, open and socially inclusive world in which the needs of the most vulnerable are met (United Nations, 2015), and inclusive rights such as education, access to services (including information) and employment for people with disabilities. Originality/value: This paper builds on existing literature and contributes to the growing body of knowledge on access by people with disabilities predicating on World Summit on Information Society principle and agenda 2030 on sustainable development goals.